Pattern of recurrence in patients with endometrial cancer: A retrospective study. Issue 9 (September 2020) - Vizza, E.; Cutillo, G.; Bruno, V.; Sperduti, I.; Mancini, E.; Baiocco, E.; Chiofalo, B.; Cicchillitti, L.; Certelli, C.; Zampa, A.; Piccione, E.; Corrado, G.
Abstract: Introduction: Endometrial cancer (EC) known prognostic factors are not sufficient to predict either outcome or recurrence rate/site: to investigate EC recurrence patterns according to ESMO-ESGO-ESTRO risk classes, could be beneficial for a more tailored adjuvant treatment and follow-up schedule. Methods: 758 women diagnosed with EC, and a 5-years follow-up, were enrolled: they were divided into the ESMO-ESGO-ESTRO risk classes (low LR, intermediate IR, intermediate-high I-HR, and highrisk HR) and surgically treated as recommended, followed by adjuvants therapies when appropriate. Results: Higher recurrence rate (RR) was significantly detected (p < 0, 001) in the HR group (40, 3%) compared to LR (9, 6%), IR (16, 7%) and I-HR (17, 1%). Recurrences were detected more frequently at distant sites (64%) compared to pelvic (25, 3%) and lymph nodes (10, 7%) recurrences (p < 0, 0001): only in LR group, no differences were detected between local and distant recurrences. 5-Year distant-free (LR 99%, IR 94%, I-HR 86%, HR 88%) and local-free survivals (LR 99%, IR 100%, I-HR 98%, HR 95%) significantly differ between groups (p < 0, 0001 and p = 0, 003, respectively). Adjuvant therapy modifies RRs only in LR group (p = 0, 01). Conclusion: To identify biological factors to stratify patients at higher risk of relapse is needed. Distant site relapse could be the main reason of endometrial cancer failure follow-up, independently or in addition to their risk class prognosis.